The Relationship Between Organizational Citizenship Behavior And Employee Productivity In University Hospitals Of Tehran Medical Sciences - Mahnaz Mayel Afshar; Ali Rajab Zadeh; Mehdi Memarpour (Tehran University of Medical Sciences, 2012)
Background and Aim: Problems such as hypothyroidism and aggressiveness may lead the organizations to reduced and seek to increase further behaviors that have the benefits for organization, such as productivity. One of the factors that produce productivity organization is organizational citizenship behavior. The aim of this study was to determine the relationship between the component of organizational citizenship behavior with human resources productivity among selected hospital's staff in Tehran University of Medical Sciences and Shahid Beheshti University of Medical Sciences. Materials and Methods: This research was carried out in 6 Hospitals of Tehran University of Medical Sciences and Shahid Beheshti University of Medical Sciences by attitude approach survey and data has been collected via questionnaire that was distributed among 429 staff of these hospitals by 2 stage stochastic sampling method. Research methodology has been descriptive, analytical and cross sectional. For survey to accept or reject the study hypothesis, was performed spearman correlation and regression tests with SPSS software. Results: The study results showed that, in our population perception, there was a significant relationship between organizational citizenship behavior and productivity in people. This means that, in these hospitals, implementation of organizational citizenship behavior has effect on the amount of peoples productivity.Conclusion: In this study, the effect of magnanimity and look over component on productivity had different results in the studied hospitals. But results are same as the initiative of individual creativity component. In addition the potential reasons for probable low levels of these components and their related indices have been analyzed and the solutions have been presented for their improvement.